قياس الاختلاف في التحصيل العلمي لطلبة جامعة بنغازي - فرع الأبيار حسب الأقسام - نجية حامد الزوي , (Scientific Journal of University of Benghazi, 2019)
The first objective of this study is to identify the factors that may affect the differences in the educational achievement of the students of Al-Abyar University .To achieve this goal, the multiple linear regression method was used, considering that the academic rate is the dependent variable. Some variables, age, sex, year of graduation, study system, section, place of residence are explanatory variables. The linear regression model is significant. The study showed that age and sex affect the rate For graduates, where the highest academic rate is among young graduates, and the female rate is higher than that of males. The second objective is to classify the graduate students according to the academic average. To achieve the second objective, we used the method of discriminate analysis. We found that age and gender are the variables that are important in the degree of discrimination and most contribute to the classification. And then find the relationship between multiple regression coefficients and Fisher coefficients obtained from the discriminate analysis .We used the data we obtained from the Fisher model to construct a multiple linear model and then tested the significance of this model.